Analysis of Puri Pati Market Parking Land Needs - Rohman, syamsul; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Abstract. Puri Market, which is located on Jalan Colonel Sunandar, precisely in the center of Pati Regency, is a traditional market which is the basis for the people of Pati to sell and buy all life-sustaining needs. This needs to be taken into account considering that the existence of an activity center must have as few parking areas as possible. Therefore, this study was carried out with the aim of providing recommendations for parking characteristics, parking space capacity and planning the most optimal parking layout for Puri Pati Market. Conditions are reviewed on 1 weekend and 3 weekdays.From 06.00 to 12.00. With the current existing motorbike parking space capacity of 280 SRP at Puri Pati Market, it can still meet existing parking needs. From the calculations that have been carried out, it is known that the need for motorbike parking space at Puri Pati Market is 345 SRP. Keywords: Market, Parking Space Capacity, SRP.